Who are the ‘gatekeepers’?: in continuation of the debate on direct applicability and direct effect of EU international agreements - Ghazaryan, Narine (Oxford University Press, 2018)
The article revisits the debate on direct applicability and direct effect of EU international agreements by questioning the role of the so called gatekeepers. It considers the established role of the Court of Justice of the EU as the gatekeeper of the EU legal order through identifying the stages of gatekeeping and their implications. It further analyses the possibilities of sidelining the Court through various techniques, which include the agreement between the parties to the international agreement. A more controversial challenge to the Court’s position stems from a practice emerging from Council decisions concluding a number of international agreements. These decisions make a strong pronouncement on the exclusion of direct effect for the entire agreement. The status of such pronouncements is analysed with reference to CJEU’s jurisprudence as well as the relevant rules of international law.